A BUSCA PELA PROTEÇÃO AO TRABALHO DOS CATADORES DE MATERIAIS RECICLÁVEIS: análise da experiência do Instituto Lixo e Cidadania em Curitiba – Pr. - Martins, Andrea Cristina (2007)
The present thesis investigated on the forms of protection to the work of the recycling materials collectors in the Brazilian society in special in the city of Curitiba/Pr. The problematic part of the discussion on the changes of the world of the work and the performance of the State in a context of advance of the liberal ideas. The research involved the discussion on the Brazilian social situacion, of low economic growth, with the emergency of the activity of recycling materials collectors, from the valuation of the materials recycle for the industry of the recycling. Diverse determination had been analyzed for emergency of the recycling materials collectors, in special the dynamics between capital and work and its consequences in the world of the work making of a landmark on urban solid residues. The performance of the Instituto Lixo e Cidadania in the city of Curitiba/Pr was analyzed in the organization of recycling materials collectors in collective arrangements, with the objective to demonstrate the profile and the demands of the recycling materials collectors. The conclusions detach the importance of the formation politics for the recognition of this category as a pledge of effective social inclusion and respect to the basic rights of the workers.